Novos indicadores para os limites do português arcaico - Silva, Rosa Virgínia Barretto de Mattos Oliveira e (2019)
This paper discusses, first, the question of periodization in the so called Historical Sciences. It focuses, specially, the problematic question of early scripta in portuguese manuscripts, recently discovered at AN-TT (Lisbon). Concerning to the final delimitation of the first documented period of Portuguese language, it presents new linguistic evidences that permit proposing the middle of the sixteenth century as a possible final limit of Old portuguese period.